Improving the yield of ‘Chok Anan’ (MA 224) mango with potassium nitrate foliar sprays - Aris, Nur Afiqah; Nulit, Rosimah; Jaafar, Hawa Z. E.; Kusnan, Misri (Taylor & Francis, 2014)
Unsynchronized flowering behavior and low fruit set are phenomenon that resulted in low production of mango fruit. The effects of a chemical inducing substance, potassium nitrate (KNO3), on enhancement of flowering on the mango clone ‘Chok Anan’ (MA 224) and, ultimately, the fruit production were studied. Initially, 12-month-old and 5-year-old mango trees were sprayed with 1%, 2%, and 5% KNO3. The 5-year-old mango trees showed earlier flowering and higher fruit set with 2% KNO3 followed by 5% and 1% KNO3. However, only 1% KNO3 initiated flowering on young mango trees. In conclusion, the flowering response to KNO3 depends on the age of tree.